Inhibition of kinesin-driven microtubule motility by monoclonal antibodies to kinesin heavy chains (The Rockefeller University Press, 1988)
We have prepared and characterized seven mouse monoclonal antibodies (SUK 1-7) to the 130-kD heavy chain of sea urchin egg kinesin. On immunoblots, SUK 3 and SUK 4 cross-reacted with Drosophila embryo 116- kD heavy chains, and SUK 4, SUK 5, SUK 6, and SUK 7 bound to the 120-kD heavy chains of bovine brain kinesin. Three out of seven monoclonal antikinesins (SUK 4, SUK 6, and SUK 7) caused a dose-dependent inhibition of sea urchin egg kinesin-induced microtubule translocation, whereas the other four monoclonal antibodies had no detectable effect on this motility. The inhibitory monoclonal antibodies (SUK 4, SUK 6, and SUK 7) appear to bind to spatially related sites on an ATP- sensitive microtubule binding 45-kD chymotryptic fragment of the 130-kD heavy chain, whereas SUK 2 binds to a spatially distinct site. None of the monoclonal antikinesins inhibited the microtubule activated MgATPase activity of kinesin, suggesting that SUK 4, SUK 6, and SUK 7 uncouple this MgATPase activity from motility.